NILAI MASJID JAMI KALI PASIR SEBAGAI SEBUAH BANGUNAN CAGAR BUDAYA: PENGAMATAN SEORANG PEJALAN KAKI - Feby Hendola (Jurnal Koridor, 2018)
Masjid Jami Kali Pasir (MJKP) is believed as the oldest mosque in Tangerang. It is located at Pasar Lama-Kali Pasir heritage site, near old Chinese settlements. In 2011 MJKP was legitimated as an architectural heritage by government of Tangerang City regardless its unnoticeable appearance and its lack of accurate historic and architecture documentary. Nevertheless the board of MJKP’s welfare mosque has tried to conserve its original parts. These facts show that MJKP has significant meaning despite its status, as an architectural heritage, is questionable. Based on this background, this writing is an attempt to know what value that MJKP contains apart from its valid historical data by experiencing its architecture and spatial conditions around it from a pedestrian’s viewpoint. Pictures of walking sequence to MJKP and interview with visitors and local people about their perception on Pasar Lama-Kali Pasir heritage site and the mosque were used to study the value. After analyzing the data with Kevin Lynch’s theory about ‘sense’ dimension, the study revealed that MJKP’s spiritual value could maintain its existence even though its physical appearance was not significant. In conclusion, the spiritual value might be essential in architectural conservation to know why an architectural heritage that has lack of historic documentary and unnoticeable appearance, such as MJKP, needs to be preserved.